Peripheral T-Cell Lymphoma: Review and Updates of Current Management Strategies - Tiffany Tang; Kevin Tay; Richard Quek; Miriam Tao; Soo Yong Tan; Leonard Tan; Soon Thye Lim (Advances in Hematology)
The classification of T-cell and natural-killer- (NK-) cell lymphomas has been updated in the 4th edition of the World Health Organization (WHO) classification of tumors of the haematopoietic and lymphoid tissue published in 2008. Based on recent epidemiological studies, NK-cell lymphomas occur almost exclusively in Asia and South America, although T-cell lymphomas appear to occur in the East as commonly as in the West. Due to the low prevalence of this disease, diagnosis and optimal treatment of patients have not been studied prospectively in large randomized trials. Nevertheless, there has been development in the understanding of T-cell lymphomas and how they should be managed; FDG-PET emerges as an increasingly important tool in diagnosis, gene-expression signatures may aid with prognostication in the future, and novel therapies are currently being studied to improve outcomes in T-cell lymphomas. More work, however, needs to be done, and international collaboration will be pertinent to deriving meaningful results from future clinical studies.